2017
DOI: 10.3390/f8050150
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Participation in REDD+ Readiness Activities for Three Collaborative Projects in Lao PDR

Abstract: Abstract:A key challenge for reducing emission from deforestation and forest degradation (REDD) in developing countries is to balance the power of various stakeholders in decision making. This study explores the forms of stakeholder participation in the implementation of three pilot projects in Laos, with a focus on who actually makes decisions on project activities. We found that stakeholder roles in making decisions were imbalanced. The central government and development partner organizations were the ones w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Benefits such as jobs and income derived from REDD + activities have been, however, rather insignificant. These questions have also been investigated in one-party countries such as Laos, where participation tends to be more restricted, and researchers argue that REDD + might be leading to improvements in participation (Boutthavong et al, 2017;Mustalahti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Benefits such as jobs and income derived from REDD + activities have been, however, rather insignificant. These questions have also been investigated in one-party countries such as Laos, where participation tends to be more restricted, and researchers argue that REDD + might be leading to improvements in participation (Boutthavong et al, 2017;Mustalahti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Farmer participation has an effect on sustainable private forest management; this shows that farmers' awareness to behave sustainably is in line with the values needed in the management of private forests. Although local communities are not the main stakeholder in decision making in most activities, their role seems to have increased in activities where participatory approaches are implemented (Boutthavong et al, 2017).…”
Section: Influence Of Community Institutions Farmer Participation Amentioning
confidence: 99%
“…The main challenge for Reducing Emissions from Deforestation and Forest Degradation (REDD) in developing countries is to balance the strengths of various stakeholder in decision making. Research by Boutthavong et al, (2017) found that the role of stakeholder in decision making is not balanced. All stakeholders must have the same knowledge and understanding of existing issues and produce collective policies, so that they can develop the concept of "fair trade" and will give influence in taking part in the benefits.…”
Section: Influence Of Community Institutions Farmer Participation Amentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, scholars have studied REDD ? in terms of stakeholder participation(Boutthavong et al 2017;Mustalahti et al 2017), land and property formalization(Dwyer and Ingalls 2015), or role of donor agencies and capacity building(Vongvisouk et al, 2016;Broegaard et al 2017).…”
mentioning
confidence: 99%